A Novel 1.31 um Narrow-band TE-Mode filter Design based on PBG Shift in 2D Photonic Crystal Slab - Farah, Lallam; Hadjira, Abri Badaoui; Mehadji, Abri (Photonics Letters of Poland, 2016)
In this letter, a novel 1.31 um narrow-band TE-Mode filter design based on photonic band gap shift in 2D photonic crystal slab with triangular lattice air holes has been proposed using the 2D-FDTD method to numerically modeling the proposed filter device. The structure is achieved by the association of three waveguides W1KA coupled in cascade arrangement within the same cell of PC with triangular lattice with single removed full row. A modulated Gaussian pulse is used to provide a wide-band excitation at any desired position inside the computational domain of the photonic crystal. The best filter configuration performances in terms of filtering and transmission is found for 60 inclusions with maximum of transmission around 80 % localized near 1.31 um Full Text: PDF References M. Zhang and N. Liaser, "Exploiting Time-Domain Approach for Extremely High Q -Factor Measurement", IEEE Transactions on Instrumentation and Measurement, 64, 10 (2015). CrossRef S. Serna, P. Colman, W. Zhang, X. Le Roux, C. Caer, L. Vivien and E. Cassan, "Experimental GVD engineering in slow light slot photonic crystal waveguides", Scientific Reports 6, Article number: 26956 (2016). CrossRef M. A. Mansouri-Birjandi, A. Tavousi and M. Ghadrdan, "Full-optical tunable add/drop filter based on nonlinear photonic crystal ring resonators", Photonics and Nanostructures - Fundamentals and Applications, 21 (2016). CrossRef Y. Zhuang, K. Ji, W. H. Chen, "Design of a DWDM Multi/Demultiplexer Based on 2-D Photonic Crystals", IEEE Phot. Tech. Lett 28, 15 (2016). CrossRef H. Abri Badaoui, M. Abri, "Optimized 1×8 compact splitter based on photonic crystal using the two-dimensional finite-difference time-domain technique", Optical Engineering 54(6), (2015). CrossRef A. Fedaouche, H. Abri Badaoui, M. Abri, "Ultra-Highly Efficient 1×3 and 1×6 Splitters for Terahertz Communication Applications", IEEE Phot. Tech. Lett, 28, 13 (2016). CrossRef A. Knapitsch, E. Auffray, C. W. Fabjan, and J. L. Leclercq, "Results of Photonic Crystal Enhanced Light Extraction on Heavy Inorganic Scintillators", IEEE Trans. Nucl. Phys. 59, 5, 2012. CrossRef M. M. Li. Weyde, D. Bozyigit, O. Yarema, and V. Wood, "Quantification of Deep Traps in Nanocrystal Solids, Their Electronic Properties, and Their Influence on Device Behavior", J. Phys. Chem. C, 120 (23), 12900?12908 (2016). CrossRef H. Abri Badaoui, M. Abri, "New Design of Integrated 2D Photonic Crystal Narrow Band Filters Using the FDTD-2D Method", Frequenz, 68 (11?12), (2014). CrossRef C. Guiffaut, A. Reineix, "Modeling of different cables types and their combinations for lightning and HIRF EMC studies in the FDTD method.", International Conference on Electromagnetics in Advanced Applications (ICEAA), (2015). CrossRef Y. Hao and R. Mittra, FDTD Modeling of Metamaterials: Theory and Applications, (Boston, Artech House, 2009). <a class="file" href="https://books.google.pl/books?hl=pl&lr=&id=uFMmAgAAQBAJ&oi=fnd&pg=PR5&dq=Y.+Hao+and+R.+Mittra,+FDTD+Modeling+of+Metamaterials:+Theory+and+Applications,+(Boston,+Artech+House,+2009).&ots=OuSTXp6bOd&sig=yaP-HMUmqkhWeSaBrjQoTGEuoZ0&redir_esc=y#v=onepage&q&f=false" target="_parent"> DirectLink E. Viasnoff-Schwoob. Propagation et Emission dans des guides multimodes a cristaux photoniques bidimensionnels. Université Paris Sud - Paris XI, 2004. DirectLink M Svaluto Moreolo, V Morra and G Cincotti, "Design of photonic crystal delay lines based on enhanced coupled-cavity waveguides", Journal of Optics A: Pure and Applied Optics, 10, 2008. DirectLink R. Ferrini, D. Leuenberger, M. Mulot, M. Qiu, J. Moosburger, M. Kamp, A. Forchel, S. Anand, and R. Houdre, "Optical study of two-dimensional InP-based photonic crystals by internal light source technique", IEEE J. of Qua. Elec, 38, (2002). CrossRef